Aortic root abscess complicating bacterial endocarditis. Demonstration by computed tomography. Issue 5 (November 1984) - Cowan, J C; Patrick, D; Reid, D S
Abstract : A 68 year old man with an aortic valve prosthesis was admitted to hospital with Staphylococcus aureus endocarditis. Despite antibiotic treatment he continued to be pyrexial. Computed tomography identified a probable abscess between the root of the aorta and the left atrium. The presence of an abscess in this location was subsequently confirmed at operation. Computed tomography is a useful additional diagnostic method for identifying this potentially lethal complication of bacterial endocarditis.